Dynamic relationship between Stock and Bond returns: A GAS MIDAS copula approach - Hoang Nguyen; Farrukh Javed (Örebro University School of Business, 2021)
Stock and bond are the two most crucial assets for portfolio allocation and risk management. This study proposes generalized autoregressive score mixed frequency data sampling (GAS MIDAS) copula models to analyze the dynamic dependence between stock returns and bond returns. A GAS MIDAS copula decomposes their relationship into a short-term dependence and a long-term dependence. While the long-term dependence is driven by related macro-finance factors using a MIDAS regression, the short-term effect follows a GAS process. Asymmetric dependence at different quantiles is also taken into account. We find that the proposed GAS MIDAS copula models are more effective in optimal portfolio allocation and improve the accuracy in risk management compared to other alternatives.
Keywords: C32; C52; C58; G11; G12; 330; GAS copulas; MIDAS; asymmetry